PEMBINAAN LITERASI MEMBACA MELALUI SELF-MOTIVATION SEBAGAI UPAYA MENINGKATKAN KOMPETENSI MENGAJAR GURU SEKOLAH DASAR KADUBERUK KECAMATAN CIOMAS SERANG - Hamidah, Hamidah; Kusuma, Jaka Wijaya; Umalihayati, Umalihayati; Rachman, Aditya; Wida, Faizatul; Audi, Nadia Putri (LPPM Universitas Bina Bangsa, 2024)
The purpose of the community service activity is to enhance the culture of reading literacy through self-motivation as an effort to improve the teaching competence of teachers, to implement technology-based learning methods, and to increase the scientific works of the teachers at SDN Kaduberuk Ciomas Serang. The implementation methods for the community service include situation and condition analysis of the target partners, preparation and transfer of science and technology, training and mentoring, partner participation, evaluation through surveys for teachers, and sustainability evaluation. The results of the community service indicate an increase in the scientific works of the teachers at SDN Kaduberuk, which positively impacts the teaching competence of the teachers by over 80%, improvement in facilities and the culture of literacy at SDN Kaduberuk, as well as an increase in reading literacy and self-motivation among teachers by over 80%. This has a positive impact on the teachers' teaching methods, which in turn positively affects the skills of their students